2017
DOI: 10.1016/j.jspd.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Attending Surgeons on Patients With Large-Curve Adolescent Idiopathic Scoliosis Undergoing Posterior Spinal Fusion

Abstract: A chart review was conducted on all eligible patients from 2009 to 2014. 47 patients were identified, 19 of whom had two attending surgeons while 28 underwent PSF performed by a single attending surgeon assisted by a resident or PA. All patients underwent similar operative procedures with pedicle-screw only constructs. Patients in the two groups underwent identical surgical and anesthetic protocols, including use of tranexemic acid. Percent EBL was calculated as EBL divided by total estimated blood volume, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…13,16,17 Five of 8 (62.5%) studies found that EBL was significantly lower in dual-attending cases, 3,13,[16][17][18] and 3 studies did not find a difference. 12,14,15 Six of 8 (75%) studies found that operative time was significantly reduced, 3,13,[15][16][17][18] and 2 studies did not find a difference. 12,14 Reporting of complications was handled very heterogeneously across included studies with regard to their definition and timing.…”
Section: Systematic Literature Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…13,16,17 Five of 8 (62.5%) studies found that EBL was significantly lower in dual-attending cases, 3,13,[16][17][18] and 3 studies did not find a difference. 12,14,15 Six of 8 (75%) studies found that operative time was significantly reduced, 3,13,[15][16][17][18] and 2 studies did not find a difference. 12,14 Reporting of complications was handled very heterogeneously across included studies with regard to their definition and timing.…”
Section: Systematic Literature Reviewmentioning
confidence: 97%
“…12,14,15 Six of 8 (75%) studies found that operative time was significantly reduced, 3,13,[15][16][17][18] and 2 studies did not find a difference. 12,14 Reporting of complications was handled very heterogeneously across included studies with regard to their definition and timing. Three studies found a lower need for PRBC transfusions in dualattending cases.…”
Section: Systematic Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations